Promotion of Unmanned Aerial Vehicles to The North American Market by Shenzhen DJI Innovation Technology Co., Ltd - Ye JIACHEN; Natalia SAKHARCHUK (Communications of International Proceedings, 2022)
The global market for unmanned aerial vehicles has been growing rapidly for over 10 years, and the market is forecast to continue to grow strongly in the coming years. The centers of development of the unmanned aerial vehicles market today are the markets of North America, China and Europe, however, other countries are also developing, but at a slower pace and volume. For the next 5 years, development trends are planned to continue, and the global drone market will grow by more than 3 times. Such a rapid development of the drone industry is associated with the active production and implementation of drones in the commercial and private sectors of society. Previously, drones were mainly produced for military purposes, however, later they quickly entered new markets, and in the modern world drones are actively used in such industries as mining, monitoring facilities, construction, aerial photography, agriculture, logistics and others. In addition, drones have become popular for private use for entertainment purposes. The introduction and use of unmanned aerial vehicles in the commercial sector has given companies more opportunities to work - increasing the quality of work by obtaining clearer and more complete information on a particular object from a drone, increasing the speed of work, and most importantly, reducing the use of manual labor and increasing employee safety in cases where previously a person himself performed complex and dangerous work related, for example, to obtaining information in life-threatening places. The relevance of the topic of the article on bringing DJI drones to the North American market lies in the fact that it is the largest and at the same time the fastest growing market for unmanned aerial vehicles. The main market is the United States, accounting for more than 75% of the production and sales of drones. The subsidiary market is Canada. Thus, the North American market is the most promising market for bringing goods to it.
Keywords: Russian-Chinese relations; development; construction; positioning strategy